PERAN KELOMPOK TANI ESA ATE DALAM USAHATANI JAGUNG DI KELURAHAN MAPANGET BARAT KECAMATAN MAPANGET KOTA MANADO - Herlan Herlin Falangi; Vicky Richard B. Moniaga; Jean Fanny Junita Timban (Sam Ratulangi University, 2020)
The purpose of this study was to determine the role of the Esa Ate Farmer Group in Corn Farming in Mapanget Barat Village, Mapanget District, Manado City, North Sulawesi Province. The research conducted from July 2019 to September 2019. Respondent selection method was Census which is all members of the Esa Ate Farmer Group, as respondent, consisting of administrators and members with a total of 15 people. Primary data collection methods were obtained from interviews and questionnaires. The research method used is a Likert scale analysis method. Whereas secondary data was obtained from the Mapanget West Kelurahan Office of Mapanget Sub-District, Manado City, North Sulawesi Province. The results showed that the Interval Criteria were on a scale of 45 to 135 or with a role status with a percentage interpretation of 60%. This shows that the Esa Ate Farmer Group still has a role both as the Learning Class and the Cooperative Forum and also has a role in procuring production facilities within the Esa Ate Farmer Group.*eprm*Â